(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the association between skin autofluorescence and obesity in patients with type 2 diabetes mellitus, and to evaluate the respective roles of skin autofluorescence and body mass index in relation to glycemic control and renal function. Methods: A cross-sectional descriptive study was conducted in 149 patients with type 2 diabetes mellitus. Participants were stratified according to body mass index (< 25 kg/m² and ≥ 25 kg/m²). Skin autofluorescence was measured using the AGE Reader mu device. Clinical and biochemical variables included body mass index, HbA1c, and estimated glomerular filtration rate. Poor glycemic control was defined as HbA1c ≥ 7%. Results: No significant difference in skin autofluorescence levels was observed between body mass index groups (p > 0.05). Lower body mass index was associated with poor glycemic control (HbA1c ≥ 7%) (OR = 0.89; p < 0.05), suggesting a “lean diabetes” phenotype. In contrast, skin autofluorescence has a correlation with age (r = 0.26; p < 0.01) and has an inverse correlation with estimated glomerular filtration rate (r = -0.31; p < 0.01). Conclusions: Skin autofluorescence was not associated with obesity status but was related to age and renal function in patients with type 2 diabetes, suggesting a potential role of skin autofluorescence as an additional marker reflecting cumulative metabolic burden.